Endoplasmic Reticulum - Català, Angel (Physiology, 2019)
The purpose of this book is to concentrate on recent developments on endoplasmic reticulum. The articles collected in this book are contributions by invited researchers with a long-standing experience in different research areas. We hope that the material presented here is understandable to a broad audience, not only scientists but also people with general background in many different biological sciences. This volume offers you up-to-date, expert reviews of the fast-moving field of endoplasmic reticulum. The book is divided in two sections: 1. Introduction and 2. Endoplasmic Reticulum Properties and Functions.